Application of terrestrial photogrammetry to the creation of a 3D model of the Saint Hedwig Chapel in the Kaňovice - Milan Mikoláš (Geodesy and Cartography, 2014)
The present article focuses on application of terrestrial photogrammetry for the purposes of creation of photogrammetric documentation of building structures with the use of digital camera – a widely accessible device. First, the article briefly describes the individual intermediate operations of the whole process leading to the creation of a three-dimensional structure. Next, attention is given to operations related to camera calibration, reconnaissance of the locality of interest, photographing itself, creation of the 3D model as well as to presentation of graphical output. In conclusion, the article focuses on determining the accuracy of photogrammetric measuring.